Methane-derived carbonate conduits from the late Aptian of Salinac (Marne Bleues, Vocontian Basin, France): Petrology and biosignatures. (September 2015) - Reitner, Joachim; Blumenberg, Martin; Walliser, Eric-Otto; Schäfer, Nadine; Duda, Jan-Peter
Abstract: Peculiar carbonate bodies occur in distinct marl layers of the Marnes Bleues Formation (Aptian–Albian, Vocontian Basin, Southern France). The carbonate conduits exhibit pipe- or sausage-like forms and a central channel. Their sizes range between 30 and 60 cm in length and 5–10 cm in diameter. The conduit carbonates consist of automicrite authigenically formed within the sediment. Millimeter-sized aggregates of framboidal pyrite are abundant within the conduit automicrites, probably representing former colonies of sulfate reducing bacteria. The central channel reflects former pathways of reduced fluids in the carbonate conduit. Ni-enrichments at the margins of the central cavity are may be due to the activity of methane-related metabolism as Ni is an important bio-element for respective microbes. Light stable carbon isotope ratios of the conduit automicrites (−25.86‰ to −23.10‰ VPDB) point to carbonate precipitation linked to anaerobic oxidation of methane (AOM), while less depleted stable carbon isotope ratios of microspar in marginal zones of the central opening (−8.96‰ VPDB) are in line with microbial sulfate reduction. A methane-related origin of the conduit carbonates is confirmed by the presence of authigenic lipid biomarkers tentatively sourced by archaea most of which are characterized by strong 13 C depletions (δ 13 C values down to −104‰). The presence of organically bound sulfur is well in line with microbial sulfate reduction. Isorenieratane potentially point to the presence of brown pigmented green sulfur bacteria. The methane was probably sourced by older OAE black shales which are known to contain isotopically (δ 13 C) heavy biomarkers of archaea as reported elsewhere. Highlights: Peculiar carbonate bodies occur in the Marnes Bleues (Aptian, Vocontian Basin). Petrography and biogeochemistry evidence formation via strong AOM. Ni enrichments and strongly 13 C depleted biomarkers highlight impact of AOM. These carbonate bodies were acting as conduits for CH4 -rich fluids. The methane was probably sourced by older OAE black shales.